PURLs: Do probiotics reduce C diff risk in hospitalized patients? - Simpson, Matthew (J Fam Pract, 2019)
A systematic review and meta-analysis says, “Yes,” but that doesn’t necessarily mean they will start appearing on hospital formularies.